Nanochip Medicine: Physical Chemistry Engineering - Hendry Izaac Elim; Long Y. Chiang (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2019)
In providing the best nanocarbon-based medicine particularly associated with their multitasking healing system, an advanced knowledge and understanding of physical chemistry engineering is compulsory. Discovery of the first spherical nanocarbon cage C60, namely, fullerene or buckyball by R. Smalley and his colleague in 1986 at Rice university made the former elected as a chemistry Nobel laureate 10 years later in 1996. Various investigations in conjunction with fullerenes had been tremendously pursued in many interesting research fields, especially, on its characters including nonlinear and optical limiting behaviors, ultrafast dynamics of electrons in 5-level models, and advanced theoretical and computational cooperation system involving fullerenes encapsulated in a carbon nanotube (CNT). This present editorial communication stimulates an alternative view of physical chemistry engineering of fullerene and its derivatives functioning as nanofullerene-based medicine and its potential healing impacts. Our aims focus on the use of such non-toxic nanocarbons for various broad application leading to a number of different medicinal products.